AN ANALYSIS OF THE ADJUSTMENT OF FIRST-YEAR STUDENTS AT STIKES ST. ELISABETH KEUSKUPAN MAUMERE IN 2024 - Marthen Preskapu Wela; Antonia Rensiana Reong (Program Studi PGSD Universitas Flores, 2025)
The success of first-year students in higher education is closely linked to their ability to adapt to the academic and social environment of college life. This study aims to identify the level of adjustment among first-year students at STIKES St. Elisabeth Diocese of Maumere and to examine differences based on demographic variables, including gender, age, and academic program. A quantitative approach with a descriptive-comparative design was employed, involving 95 participants selected through accidental sampling. Data were collected using the Student Adaptation to College Questionnaire (SACQ), which has been validated and proven reliable. The results indicate a generally good level of student adjustment, with the highest scores found in academic and institutional dimensions. Independent t-tests and ANOVA revealed significant differences based on gender (p = 0.016) and academic program (p = 0.004), but not age (p = 0.164). These findings highlight the need for adaptive support strategies that consider gender-specific and program-specific characteristics to enhance student adjustment and academic success.